2023
DOI: 10.1021/acs.inorgchem.3c01315
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Primary Explosive by Self-assembly of Combustible and Oxidizing Agents under Acid

Abstract: In order to further explore the effect of ligands on the performance of primary explosives and gain a deeper understanding of the coordination mechanism, we designed furan-2-carbohydrazide (FRCA), a ligand, by using oxygen-containing heterocycles and carbohydrazide. Then, FRCA and Cu­(ClO4)2 were used to synthesize coordination compounds [Cu­(FRCA)2(H2O)­(ClO4)2]·CH3OH (ECCs-1·CH 3 OH) and Cu­(FRCA)2(H2O)­(ClO4)2 (ECCs-1). The structure of the ECCs-1 was confirmed by single-crystal X-ray diffraction, IR and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The test results showed that the peak thermal decomposition temperature of ECCs-1 was 215.6 °C, which was higher than those of the previously reported [Cu(PZCA) 2 ](ClO 4 ) 2 , 25 [Cu-(HDMPZCA) 2 (ClO 4 ) 2 ](ClO 4 ) 2 ·2H 2 O, 26 and Cu(FRCA) 2 (H 2 O)(ClO 4 ) 2 . 27 The reason may be the low enthalpy of pyridine ring formation, which was more stable than other heterocyclic ligands. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The test results showed that the peak thermal decomposition temperature of ECCs-1 was 215.6 °C, which was higher than those of the previously reported [Cu(PZCA) 2 ](ClO 4 ) 2 , 25 [Cu-(HDMPZCA) 2 (ClO 4 ) 2 ](ClO 4 ) 2 ·2H 2 O, 26 and Cu(FRCA) 2 (H 2 O)(ClO 4 ) 2 . 27 The reason may be the low enthalpy of pyridine ring formation, which was more stable than other heterocyclic ligands. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…They are an interesting class of HEDMs that are still receiving a lot of attention because of their potential and multipurpose applications . These energetic materials have many advantages such as easier synthesis routes, higher heat of formation, good thermal stability, easier modification, and lower vapor pressures . This procedure can greatly increase the number of available energetic materials.…”
Section: Introductionmentioning
confidence: 99%